J. Krishnamurti: Educator for peace - Meenakshi, Thapan (London Routledge, 2022)
Teacher, thinker, writer, and speaker, J. Krishnamurti (1985-1986) was an Indian educationist, spiritual leader, and a key figure in world philosophy. He raised significant questions about the state of the world, about our tendency to remain passive, conditioned and in a state of overwhelming confusion about how we relate to the world. Through talks and writings spread over many decades and geographical locations, he articulated an unconditioned, reflective approach which emphasized self-inquiry. This volume provides an understanding of Krishnamurti's views on the human predicament in a disintegrating world, marked by conflict, divisions, wars, and climate change. It also examines his educational thought and its enormous potential for change. Krishnamurti argued that our minds are so conditioned that we are unable to look, listen or learn without our prior knowledge that foregrounds the role of memory and time. He highlighted the need to work with young children, with a special focus on the school as the centrepiece of his perception for psychological development and educational excellence. It is within an educational setting that Krishnamurti hoped that the seeds for individual and social change will be catalysed. An introspective look at the life and legacy of an eminent 20th century thinker, this volume will be of great interest to students and researchers of philosophy, education, religion and spirituality, South Asia studies, modern history, and the social sciences
Keywords: Peace; Education--Philosophy; Philosophers--India--Biography